Meta Analisis Platform Media Digital Ramah Penyandang Disabilitas - Albertus Magnus Prestianta; FX Lilik Dwi Mardjianto; Hargyo Tri Nugroho Ignatius (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
One of the main functions of mass media is providing information. At the same time, the access to information is everyone's right. Therefore, the mass media have to open the possibilities for people to access information, including disabled people. Act. Number 8 of 2016 concerning disabled people also mandates this right. The act will come into force in 2018, so various parties need to make various preparatory efforts, including conducting research. This study aims to map online news sites that are friendly and unfriendly to disabilities. To achieve this goal, researchers use standards in the Web Content Accessibility Guidelines (WCAG) to map online media in Indonesia that are friendly to access for disabled people. To obtain this information the researchers conducted a quantitative study of 62 cyber media sites in Indonesia by measuring the level of accessibility of the media to disabled people. The findings indicate that there are no cyber media sites in Indonesia that are friendly to access for disabled people. Sites like Riau24.com, Manadonews.co.id and Ayobandung.com are sites with the highest percentage of success among the 62 sites analyzed.